Pemanfaatan Calcium Carbide dan Bottom Ash sebagai Bahan Subtitusi pada Beton - Ermita Datu Puang; Frans Phengkarsa; Lisa Febriani (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The purpose of this research is to find out how to use calcium carbide and bottom ash as substitution materials in concrete. Where calcium carbide is a colorless chemical compound with the chemical formula (CaC2), and the calcium carbide that is often used is generally gray or brown in color. while bottom ash is bottom ash that is released under the combustion furnace from the remaining coal combustion. The percentage of using 10% calcium carbide as a substitute for cement and bottom ash as a substitute for fine aggregate is 25%, 30% and 35%. In this study, a cylindrical specimen was used with a diameter of 15 cm and a height of 30 cm, and a block with a size of 15 cm × 15 cm × 60 cm. The method used in this study is the ACI (American Concrete Institute) method with a planned concrete quality of 30 MPa. The compressive strength test results at 28 days obtained results at variations of 25%, 30% and 35%, namely 30,951 MPa, 31,328 MPa, and 32,838 MPa. The split tensile strength test results at variations of 25%, 30% and 35% were 2.878 MPa, 2.972 MPa and 3.161 MPa. The results of the flexural strength test at variations of 25%, 30% and 35% are 3,338 MPa, 3,390 MPa, 3,441 MPa. The test results show that the use of calcium carbide and bottom ash substitution complies with the 30 MPa quality plan.